2015
DOI: 10.5935/0034-7280.20150026
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and treatment of cystoid macular edema after cataract surgery

Abstract: O edema macular cistoide é uma das principais causas de baixa de visão após cirurgia de catarata. O processo inflamatório parece ser o principal fator causal do edema. São considerados fatores de risco complicações cirúrgicas, doenças retinianas prévias, diabetes, uveítes e uso de colírios de prostaglandinas. O diagnóstico é feito clinicamente, mas a angiografia fluoresceínica e a tomografia de coerência óptica também são ferramentas importantes para detectar o edema e auxiliar no diagnóstico diferencial. Apes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The management of pseudophakic cystoid macular edema (PCME) usually done by topical application of NSAIDs and steroids before and after surgery, and subconjunctival triamcinolone can be considered in diabetic patients, 5 in case of treatment failure, then switching to posterior subtenon or intravitreal steroids are recommended. 6 However, when the vitreomacular traction is the leading force for cystic macular edema formation, then pars plana vitrectomy is recommended if the spontaneous release does not happen within months, especially in cases of moderate visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…The management of pseudophakic cystoid macular edema (PCME) usually done by topical application of NSAIDs and steroids before and after surgery, and subconjunctival triamcinolone can be considered in diabetic patients, 5 in case of treatment failure, then switching to posterior subtenon or intravitreal steroids are recommended. 6 However, when the vitreomacular traction is the leading force for cystic macular edema formation, then pars plana vitrectomy is recommended if the spontaneous release does not happen within months, especially in cases of moderate visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller increase in macular thickness and less loss of contrast sensitivity might exist, thereby justifying the use of NSAIDs for high-risk patients. 20 However, a recent study concluded that the risk of CME in patients who underwent cataract surgery was low and that the reduction with the use of anti-inflammatory drugs was modest. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in cataract surgery, such as microincision and new phacoemulsification techniques, CME may occur even in uncomplicated surgeries. 1 The incidence of acute, visually significant CME has been reported from 1% to 2% of patients following uncomplicated phacoemulsification. 2,3 In diabetic patients, macular edema is the main cause for low visual acuity.…”
Section: Introductionmentioning
confidence: 99%